Blather, Razzle and Dada: Contextualizing Brian O'Nolan's Early Journalism. Issue 2 (May 2019) - Harris, Tobias
Abstract : This essay develops recent critical discussions of Brian O'Nolan's short-lived comic periodical, Blather, by further contextualizing the magazine amidst the popular and avant-garde print culture of its period. First, I undertake a detailed comparison of Blather with the English comic periodical Razzle, revealing the features which are lifted directly from this model and exploring the significance of Razzle 's use of metaleptic humour for O'Nolan's work more widely. Subsequently, I place Blather in the context of the publications and activities of the Berlin Dadaists and specifically their magazine Der Dada . I propose three characteristics it shares with Blather : what I term the 'extended identity trope'; the subversion of popular culture with photomontage techniques; and an engagement with the creative possibilities of advertising. In conclusion, I propose that these contexts shed light on the cohabitation of modernist experimentation and a popular orientation which characterises Blather and O'Nolan's wider literary project.